Forty Years Later: Translating Erotic Writing Into a Different Age - Zorzetto, Marina (Université d'Ottawa / University of Ottawa, 2021)
In 1981, only two years after the end of the harshest years of government censorship in Brazil, the controversial erotica writer Cassandra Rios published the novel “Eu sou uma Lésbica” (I am a Lesbian), which is considered to this day her most polemical book. After being censored multiple times and consequently bankrupted by the military dictatorship for writing about female, and more specifically lesbian, sexuality, it seems that Rios saw the relaxation of censorship laws as a way of taking revenge on the system that had persecuted her for years. She released a book with much more subversive topics than her usual output. The book narrates the coming of age of a lesbian living in São Paulo, and presents themes like violence against LGBT people, pedophilia, fetishism, and the narrator’s perceptions of discrimination. This thesis is based on the translation of this work for a Canadian 2020 audience. In it, I discuss the specificities involved in translating into one’s second language, the choices regarding adaptation of cultural aspects of a source text that comes from a culture considered more marginal than the target one, the issues that the translator goes through when faced with sensitive topics, and the political power of female-written erotica.
Keywords: Translation